Motion analysis of Kolman technique by Korean top gymnasts on horizontal bar - Lim, K.-C.; Lee, N.-K. (Korean Journal of Sport Biomechanics, 2021)
Objective: The aim of this study was to analyze the pattern of Kolman technique by five Korean top gymnasts including the three national athletes on horizontal bar. Method: Two digital high-speed camcorders were used with 90 frames/sec and their Kolman motions were filmed in sports science secondary school gymnasium at U city. After the kinematic and kinetic variables were carried out by Kwon3D 3.1 motion package during the whole phase, the optimized release motion was investigated by simulating the body COG path during the aerial phase. Results: Firstly, it was revealed that the average changes of hip, shoulder joint angle were 84 deg, 53 deg respectively during the functional sub-phase and the average swing phaseal time was 1.21 s. Secondly, it was revealed that the average body COG positions and velocities (Y, Z) at release were -0.65 m, 0.48 m, 1.65 m/s, 3.97 m/s respectively and the average release angle, peak height and flight time were 67 deg, 1.29 m, 0.79 s respectively. Thirdly, it was revealed that the directions of somersault of whole and lower body, tilt of lower body were counterclockwise, whereas the directions of tilt of whole body, twist of whole and lower body were clockwise at the ready for re-grasp. Lastly, it was revealed that the body COG paths were different from each other during the aerial phase followed by the different body COG velocities. Conclusion: Korean gymnasts of this study controlled their motions well in terms of the timing of hip·shoulder joint, body position, body angular momentum especially during the functional sub-phase, but their motions were different during the aerial phase. Nonetheless most of them made the adequate body position at the instant of re-grasp. It would be suggested that Korean gymnasts except S3 should increase the vertical velocity.